Associations of individual and combined physical activity and body mass index groups with proinflammatory biomarkers among colorectal cancer patients - Himbert, Caroline; Warby, Christy A.; Gigić, Biljana; Ose, Jennifer; Lin, Tengda; Viskochil, Richard; Peoples, Anita R.; Ashworth, Anjelica; Schrotz-King, Petra; Scaife, Courtney L.; Cohan, Jessica N.; Jedrzkiewicz, Jolanta; et al. (Cancer epidemiology, biomarkers & prevention, 2022)
Physical activity and obesity are well-established factors of colorectal cancer risk and prognosis. Here, we investigate associations of individual and combined physical activity and body mass index (BMI) groups with proinflammatory biomarkers in colorectal cancer patients.Self-reported physical activity levels were classified as “active” (≥8.75 MET-hours/week) versus “inactive” (<8.75 MET-hours/week) in n = 579 stage I-IV colorectal cancer patients enrolled in the ColoCare Study. BMI [normal weight (≥18.5-<25 kg/m2), overweight (≥25-<30 kg/m2), and obese (≥30 kg/m2)] was abstracted from medical records. Patients were classified into four combinations of physical activity levels and BMI. Biomarkers [C-reactive protein (CRP), SAA, IL6, IL8, and TNFα] in presurgery serum samples were measured using the Mesoscale Discovery Platform. Regression models were used to compute relative percent differences in biomarker levels by physical activity and BMI groups.“Inactive” patients had non-statistically significant higher IL6 levels compared with “active” patients (+36%, P = 0.10). “Obese” patients had 88% and 17% higher CRP and TNFα levels compared with “normal weight” patients (P = 0.03 and 0.02, respectively). Highest CRP levels were observed among “overweight or obese/inactive” compared with “normal weight/active” patients (P = 0.03).We provide evidence of associations between individual and combined physical activity and BMI groups with proinflammatory biomarkers. Although BMI was identified as the key driver of inflammation, biomarker levels were higher among “inactive” patients across BMI groups.This is the largest study in colorectal cancer patients investigating associations of energy balance components with inflammatory biomarkers. Our results suggest that physical activity may reduce obesity-induced inflammation in colorectal cancer patients and support the design of randomized controlled trials testing this hypothesis.